Seaweed Polysaccharides and Derived Oligosaccharides Stimulate Defense Responses and Protection Against Pathogens in Plants - Moenne-Munoz, A; Gonzalez-Figueroa, A (2011)
Plants interact with the environment by sensing "non-self" molecules called elicitors derived from pathogens or other sources. These molecules bind to specific receptors located in the plasma membrane and trigger defense responses leading to protection against pathogens. In particular, it has been shown that cell wall and storage polysaccharides from green, brown and red seaweeds (marine macroalgae) corresponding to ulvans, alginates, fucans, laminarin and carrageenans can trigger defense responses in plants enhancing protection against pathogens. In addition, oligosaccharides obtained by depolymerization of seaweed polysaccharides also induce protection against viral, fungal and bacterial infections in plants. In particular, most seaweed polysaccharides and derived oligosaccharides trigger an initial oxidative burst at local level and the activation of salicylic (SA), jasmonic acid (JA) and/or ethylene signaling pathways at systemic level. The activation of these signaling pathways leads to an increased expression of genes encoding: (i) Pathogenesis-Related (PR) proteins with antifungal and antibacterial activities; (ii) defense enzymes such as pheylalanine ammonia lyase (PAL) and lipoxygenase (LOX) which determine accumulation of phenylpropanoid compounds (PPCs) and oxylipins with antiviral, antifugal and antibacterial activities and iii) enzymes involved in synthesis of terpenes, terpenoids and/or alkaloids having antimicrobial activities. Thus, seaweed polysaccharides and their derived oligosaccharides induced the accumulation of proteins and compounds with antimicrobial activities that determine, at least in part, the enhanced protection against pathogens in plants. © 2011 by the authors; licensee MDPI.